A simple cell transport device keeps culture alive and functional during shipping. (21st June 2017) - Miller, Paula G.; Wang, Ying I.; Swan, Glen; Shuler, Michael L.
Abstract : Transporting living complex cellular constructs through the mail while retaining their full viability and functionality is challenging. During this process, cells often suffer from exposure to suboptimal life‐sustaining conditions (e.g. temperature, pH), as well as damage due to shear stress. We have developed a transport device for shipping intact cell/tissue constructs from one facility to another that overcomes these obstacles. Our transport device maintained three different cell lines (Caco2, A549, and HepG2 C3A) individually on transwell membranes with high viability (above 97%) for 48 h under simulated shipping conditions without an incubator. The device was also tested by actual overnight shipping of blood brain barrier constructs consisting of human induced pluripotent brain microvascular endothelial cells and rat astrocytes on transwell membranes to a remote facility (approximately 1200 miles away). The blood brain barrier constructs arrived with high cell viability and were able to regain full barrier integrity after equilibrating in the incubator for 24 h; this was assessed by the presence of continuous tight junction networks and in vivo‐like values for trans‐endothelial electrical resistance (TEER). These results demonstrated that our cell transport device could be a useful tool for long‐distance transport of membrane‐bound cell cultures and functional tissue constructs. Studies that involve various cell and tissue constructs, such as the "Multi‐Organ‐on‐Chip" devices (where multiple microscale tissue constructs are integrated on a single microfluidic device) and studies that involve microenvironments where multiple tissue interactions are of interest, would benefit from the ability to transport or receive these constructs. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:1257–1266, 2017